Neuroethics: the reign of neuroscience begins in the foundation of the ethics - Figueroa, Gustavo (Acta Bioethica, 2022)
1] The Neuroscience of Ethics constitutes a progress when applying empirical science in the investigation of the moralphenomenon. 2] Emphasizing the importance of affects and feelings represents a compensation for the excessive importancegiven to reason in the formation of moral judgments. 3] There are serious methodological difficulties by not specifying theconcepts of intuition, affections, duty and especially what is understood by ethics. 4] But scientific research apprehends manas an “entity” in himself (present) and not as an “existence” (future), that is, being-in-the-world. 5] Instead of “having” amoral, the human being “is” moral and as such is a project thrown towards its most authentic possibility that consists ofappropriating its being-for-death.